A high-fidelity CFD-based model for the prediction of ship manoeuvrability in currents. (15th July 2022) - Kim, Daejeong; Tezdogan, Tahsin; Incecik, Atilla
Abstract: The manoeuvring behaviour of a vessel in currents differs remarkably from its behaviour in water without a current, stemming from hydrodynamic effects caused by the presence of the current. Given that vessels operating in open seas and coastal waters are mostly exposed to ocean currents, it is important to have an understanding of the influence of currents on ship manoeuvrability. In the present paper, by means of an unsteady Reynolds-Averaged Naiver-Stokes solver, a numerical study of ship manoeuvrability in different currents was performed. Firstly, a model-scale container ship (the KRISO Container Ship) was used to develop the Computational Fluid Dynamics (CFD) model capable of performing a self-propelled free manoeuvre. Then, a validation study was carried out to assess the validity of the CFD model by comparison with the available experimental results from a free-running test. Following this, a series of manoeuvring simulations (i.e., standard turning manoeuvres) in deep waters with current speed to ship speed ratios varying between −0.552 and −0.138/+0.138 and + 0.552 were conducted using the present CFD model. The numerical results demonstrated that the inclusion of the current has a remarkable influence on the turning performance of the ship, leading to significant changes in the ship trajectory and its turning parameters when compared to the inherent ship manoeuvrability in deep water without a current. Highlights: Free-running CFD simulations were performed to evaluate the turning performance of the KCS in currents. A validation study was carried out to assess the validity of the CFD model. The inclusion of the current has a remarkable influence on the turning performance of the ship. It is highly believed to offer a deeper understanding of the ship manoeuvrability in currents.